2022
DOI: 10.1590/1980-265x-tce-2022-0139pt
|View full text |Cite
|
Sign up to set email alerts
|

Análise Do Transtorno Do Estresse Pós-Traumático Em Profissionais De Enfermagem Durante a Pandemia Da Covid-19

Abstract: RESUMO Objetivo analisar a prevalência de Transtorno de Estresse Pós-Traumático e os fatores associados ao desenvolvimento do Transtorno de Estresse Pós-Traumático em profissionais de enfermagem durante a pandemia da COVID-19. Método estudo observacional, analítico e transversal, realizado com 309 profissionais de enfermagem, utilizando questionário para avaliar dados sociodemográficos e informações sobre o trabalho, além da Escala do Impacto do Evento - Revisada (IES-R), que visa coletar informações relaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 17 publications
0
1
0
2
Order By: Relevance
“…In the actual investigation, the level of stress was high among the participants, especially in the ‘interpersonal relations’ domain. Previous evidence showed that nurses who worked on the frontline were more prone to higher levels of stress due to the conflicts and ambiguities of roles that they were expected to develop [ 35 , 36 ]. This occupational exposure can have negative impacts on psychological, emotional, and social aspects, as described in an integrative review of the literature conducted in 2022 [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the actual investigation, the level of stress was high among the participants, especially in the ‘interpersonal relations’ domain. Previous evidence showed that nurses who worked on the frontline were more prone to higher levels of stress due to the conflicts and ambiguities of roles that they were expected to develop [ 35 , 36 ]. This occupational exposure can have negative impacts on psychological, emotional, and social aspects, as described in an integrative review of the literature conducted in 2022 [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Em relação a elevada exposição ao COVID-19, os profissionais demonstraram sentimentos de tensão, medo e preocupação em virtude do tempo distendido de serviço. Estes sentimentos desenvolvidos pelos profissionais de enfermagem estão associados à elevadas taxas de mortalidade, exposição repetidas a eventos traumáticos e privação de diretrizes de tratamento eficiente (Almeida et al, 2022).…”
Section: Introductionunclassified
“…Centro Universitário Maurício de Nassau (UNINASSAU), Juazeiro do Norte -CE 2. Universidade Regional do Cariri (URCA), Crato -CE 3.…”
unclassified